Analisis Akuntabilitas dan Tranparansi Pengelolaan Dana Pemirak Melalui Peranan Kearifan Budaya Lokal Pangentos Ayahan Adat (Studi Kasus Pada Desa Adat Padang Bulia Kecamatan Sukasada Kabupaten Buleleng) - I Gusti Agung Wahyu Krisna Mukti Pratama; Anantawikrama Tungga Atmadja (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2020)
Pemirak is a financial policy given by the customary village in which the villagers who cannot do their duty for the village or known as haturang ngayah are required to pay the agreed nominal amount based on its criteria. As a non-public organization managing the funds of Pemirak, the customary village should take responsibility for the accountability and transparency of financial management. This study was conducted to find out (1) the accountability process done by the customary village of Padang Bulia related to maintaining the accountability and the transparency of the funds of Pemirak, (2) The comprehension of the people who were active in Pemirak management regarding the principles of accountability and transparency in the management of the collected funds. This study was conducted using the qualitative method and took place in the customary village of Padang Bulia, Sukasada sub-district of Buleleng regency.  Primary data and secondary data were used in this study. The results found in this study showed (1) The financial management process of the funds of Pemirak was done through several stages, namely acceptance, consumption and reporting in which the accountability and the transparency in financial management have done by the management of the customary village of Padang Bulia by submitting a recapitulation report on income and expenditure during the meeting called Sangkepan which is then discussed in the next meeting known as Paruman, and (2) The accountability in the management of the funds of Pemirak has included transparency, obligations, control, responsibility, and responsiveness.